2013
DOI: 10.1111/pops.12063
|View full text |Cite
|
Sign up to set email alerts
|

“Victims” Versus “Righteous Victims”: The Rhetorical Construction of Social Categories in Historical Dialogue Among Israeli and Palestinian Youth

Abstract: Informed by social identity theory and a rhetorical approach to the study of social category construction in social interaction, this study analyzed the nature and function of participant utterances in two conditions of intergroup dialogue about history between Israelis and Palestinians. Across conditions that sought to either emphasize recategorization into a common in-group identity or subcategorization into mutually differentiated identities, Palestinian and Arab Israeli utterances primarily reflected the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…Our study compared two competing approaches to dialogue within intergroup contact rooted in social psychological theories (see also Pilecki & Hammack, ). Our intent was not to provide a definitive answer to which of these competing approaches is more valuable in a conflict setting or which achieves some particular outcome that can be causally isolated to the contact paradigm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study compared two competing approaches to dialogue within intergroup contact rooted in social psychological theories (see also Pilecki & Hammack, ). Our intent was not to provide a definitive answer to which of these competing approaches is more valuable in a conflict setting or which achieves some particular outcome that can be causally isolated to the contact paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…However, little research has systematically varied the paradigm of dialogue facilitated in order to see whether a particular form of dialogue‐based contact might more effectively challenge existing power asymmetries. Recently, Pilecki and Hammack () found that Jewish Israeli and Palestinian youth engage in a consistent pattern of competitive victimization when discussing history regardless of the facilitation paradigm used. The MD paradigm, particularly as developed and put into practice in Israel at the School for Peace, is explicitly intended to empower the lower status group in the encounter (Halabi & Sonnenschein, ).…”
Section: How Does the Experience Of Contact Vary By Nationality?mentioning
confidence: 99%
“…We prefer to think of these types of master narratives as their own distinct "kind," chiefly because we place great emphasis on the process of social categorization and its implications for human development in all of our work [e.g., Pilecki & Hammack, 2014;. In our view, subsuming the social-categorical master narrative within the biographical privileges personal identity by suggesting that individual cognition about the life story precedes consideration of social cognition.…”
mentioning
confidence: 99%
“…Hammack, Pilecki, and Merrilees (2013) found evidence that the goals of the confrontational model, particularly increased self-examination, awareness of intergroup difference, and acknowledgment of power asymmetries between groups, were reported by a sample of Israeli, Palestinian and US youth participating in dialog. Pilecki and Hammack (2013), however, found little difference in the historical narratives constructed by Israeli and Palestinian youth participating in dialog employing either a coexistence or confrontational model. Results revealed a common pattern across models; namely, both Israelis and Palestinians deployed historical narratives to compete for the title of "victim" within the conflict and gain the moral status that it entailed.…”
Section: Dialog-based Contact Among Israelis and Palestiniansmentioning
confidence: 82%
“…In studies examining integrated Jewish-Palestinian bilingual schools in Israel, Bekerman and colleagues have found that, despite efforts to provide an integrated curriculum legitimizing both historical narratives, hegemonic and exclusivist collective narratives and identities inevitably emerged (Bekerman, 2008(Bekerman, , 2009aBekerman & Maoz, 2005;Bekerman & Zembylas, 2010). Pilecki and Hammack (2013) discovered that, within the context of intergroup dialog, exclusivist narratives of history can facilitate processes of competitive victimhood as both groups emphasize instances of outgroup harm toward the ingroup.…”
Section: Historical Narrative and National Identitymentioning
confidence: 99%